Crítica da razão clínica - contribuições à daseinsanálise: fundamentação, prática e psicopatologia epocal - Ong, Lucas Francis e Silva (2022)
There are some peculiarities that make daseinsanalysis different from traditional psychoanalysis. If psychoanalysis operates on assumptions of a psychic order, daseinsanalysis operates on the suspension of all attributes linked to the human; there is no theory, but a description of the fundamental conditions of existence, which is carried out by Heidegger in Being and time in the analytics of being-there. Explanatory principles and systems are, therefore, replaced by ontological conditions of existence. The fundamental conditions are always comprehensively updated and implemented within a factual world. In this context, the objective of the present work is to think about new paths and developments of daseinsanalysis, both in its ontological foundation and in its clinical-therapeutic application, which will be thought from the phenomenological method. Thus, to access clinical phenomena, one must always move from ontological conditions to the factual concretions, in a reconciliation of the universal with the particular. Daseinsanalysis thus conquers the political, cultural and situational space, having to operate not exclusively on the fundamental ontology, but on the epochal developments of our situation. The research is thus conducted towards an ontology of the present and an epochal psychopathology, starting to think from clinical cases on the link between fundamental ontology, criticism of the present and the singularity of the clinical cases. This work was carried out with the support of the Conselho Nacional de Desenvolvimento Científico e Tecnológico — Brasil (CNPq) and Fundação São Paulo — FUNDASP — São Paulo, Brazil